Molecular structure model construction and quantum chemical calculations for weakly caking coal: a case study of Huangling coal in Shaanxi, China - Hongqing Zhu; Rui Li; Binrui Li; Jiashuo Wang; Lintao Hu; Baolin Qu; Linhao Xie; Lei Zhang (Fuel, 2027)

Rapid quantitative analysis method for paraffin content in crude oil based on NIR-MIR spectral fusion strategy combined with ensemble learning modeling - Maogang Li; Xuedong Chen; Linhao Li; Chunhua Yan; Tianlong Zhang; Hua Li (Fuel, 2026)

Integration of nontargeted screening with in vitro bioassays to evaluate and identify estrogenic compounds in food contact materials - Hongyan Li; Linhao Ying; Ya Chen; Wendi Fang; Yuxia Hu; Chao Deng; Lei Zhao; Jiangdong Zhang (Food Chemistry, 2026)

A Time Series Prediction Method for Ocean Sound Speed Profiles Based on Improved TCN Neural Network and Its Application in Seafloor Geodetic Positioning - Yueyuan Ma; Shuang Zhao; Baojin Li; Linhao Li (Journal of Marine Science and Engineering, 2026)
Ocean sound speed profile (SSP) is a key parameter for underwater acoustic detection, remote sensing, and seafloor geodetic positioning, and its temporal prediction is essential for improving acoustic positioning accuracy. Conventional direct measurements are inefficient and spatially sparse, while statistical and acoustic inversion methods fail to capture the strong nonlinear evolution of the sound speed field. Among existing time series models, LSTM, a recurrent network for time series forecasting, lacks an explicit receptive field. In contrast, the original TCN, a temporal convolutional network with dilated convolutions, poorly captures local fine structures and relies heavily on empirical tuning. To overcome these limitations, we propose an improved TCN-based SSP prediction method and apply it to seafloor geodetic positioning. The approach first constructs a sound speed increment field via first-order time differencing to remove global trends and highlight local variations. It then employs Optuna (version 4.9.0), a Bayesian sampling-based automatic optimization framework, to automatically tune key TCN parameters within a predefined search space, reducing reliance on manual tuning. The predicted high-resolution sound speed time series is finally used for ray tracing positioning to enhance seafloor geodetic accuracy. Experiments on the GLORYS12V1 reanalysis dataset show that LSTM and the original TCN achieve root mean square error (RMSE) and mean absolute error (MAE) values of 0.414 and 0.299 m/s, as well as 0.360 and 0.258 m/s, respectively, whereas our improved TCN reduces these to 0.205 and 0.131 m/s, substantially outperforming both baselines. In simulated Global Navigation Satellite System–Acoustics (GNSS-A) seafloor positioning, the 3D positioning RMSE drops to about 0.075 m, with improved stability. The proposed method offers an effective solution for accurate SSP time series forecasting and high-precision seafloor geodesy.

Coordinated optimization of 3′-phosphoadenosine-5′-phosphosulfate (PAPS) supply and sulfotransferase expression in Escherichia coli for production of chondroitin sulfate A with high sulfation degree - Hejia Qi; Lei Shi; Lingxin Huang; Xiangting Song; Linhao Zhang; Weiwei Meng; Cong Gao; Guipeng Hu; Jia Liu; Zhimeng Wu; Jing Wu; Xiaomin Li (Carbohydrate Polymers, 2026)

Propeller ice accretion effects on tandem propeller aerodynamics in eVTOL aircraft mode - Ghulam Ishaque; Linhao Li; Junli Wang; Jian Wu (Cold Regions Science and Technology, 2026)

Early Paleozoic Affiliation between South China Block and Gondwana Revealed by Early Silurian Remagnetization - Min Zhang; Yan Liu; Huafeng Qin; Jinhua Li; Yifei Hou; Bitian Wei; Wei Liu; Linhao Cui; Xingliang Zhang; Chenglong Deng; Yongxin Pan (Journal of Earth Science, 2026)

Study on the influencing factors of pre-oxidized water-immersed coal under oxygen-lean conditions re-ignition by mathematical statistics and other methods: Microscopic and macroscopic insights - Houwang Wang; Hongqing Zhu; Jiahao Duan; Binrui Li; Linhao Xie; Jie Zhang; Ruike Jin (Fuel, 2026)

A double-filter driving cycle generation framework with dynamometer testing and analysis - Nan Xu; Qiao Liu; Chengyin Yuan; Yongtao Yang; Yan Kong; Yifan Jia; Linhao Li; Jincheng Li (Transportation Research Part D: Transport and Environment, 2026)

Micropillar-patterned electrodes to enhance mass transfer in low Pt-loaded fuel cells - Yuan Wang; Linhao Fan; Yongkang Luan; Qing Du; Yalin Zhang; Xing Li; Meng Ni; Fang Liu; Zhongjun Hou; Kui Jiao (Science Bulletin, 2026)

Synergistic activation of peracetic acid by ultra-low-dose Co/Mn dual active sites for efficient pollutant degradation via multiple reactive pathways - Xiaohui Zhang; Jia Wei; Xiruo Niu; Yanan Li; Linhao Wang; Jiamei Li; Nan Cui; Jiangkai Huo; Wei Ji; Yvxin Zhao; Wenhao Yan; Jun Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Atomic scale characterization of oxidation path of active functional groups and formation of by-products in coal regulated by oxygen concentration: Experimental and molecular dynamics simulation - Binrui Li; Tianyu Li; Xin Li; Hongqing Zhu; Haoyu Zhang; Linhao Xie; Baolin Qu (Fuel, 2026)

Effects of enhanced circadian lighting on well-being among older adults: Pilot data from a 16-week placebo-controlled trial - Linhao Li; Robbert J. Klein; Kevin A. Mazurek; Christina Y. Chen; Eric M. Snyder (Building and Environment, 2026)

Thermodynamic Analysis and Dynamic Evolution of Microscopic Physicochemical Properties During the Oxidation Process of Low-Rank Coal - Linhao Xie; Hongqing Zhu; Rui Li; Lei Zhang; Qi Yuan; Tianyu Li; Houwang Wang (Natural Resources Research, 2026)

A review of recent advances in methods for extracting broadband surface waves from ambient noise data - Yingjie Yang; Zhengyang Li; Tongtong Xie; Jinyun Xie; Xiangyang Chen; Linhao Zhou; Guoliang Li (Science China Earth Sciences, 2026)

Response mechanism of dominant reactive functional groups in lignite under hypoxic conditions: a study combining phased microstructural and energy changes - Binrui Li; Mangu Hu; Hongqing Zhu; Houwang Wang; Linhao Xie; Tianyu Li; Saiyi Gao; Baolin Qu (Fuel, 2026)

miR-203 Alleviates Myocardial Damage Caused by Acute Coronary Syndrome by Inhibiting CA125 - Yanfang Guo; Jinlin Li; Linhao Zhang (Biochemical Genetics, 2026)

Electrospun nanofiber electrodes for low platinum-loaded fuel cells - Linhao Fan; Yongkang Luan; Lei Xing; Qing Du; Jin Xuan; Yuan Wang; Fan Zhang; Xing Li; Shuheng Yuan; Chasen Tongsh; Siyuan Wu; Kui Jiao (Science Bulletin, 2026)

D-band center engineering of cobalt-modified Cu@C for enhanced peracetic acid activation toward efficient water decontamination via synergistic radical/non-radical pathways - Wenhao Yan; Jia Wei; Nan Cui; Yuxin Zhao; Xiaohui Zhang; Jiamei Li; Linhao Wang; Yanan Li; Sairui Guan; Jun Li; Ju Wang (Chemical Engineering Journal, 2026)

Evaluation and prediction of atmospheric environmental carrying capacity in an Inland urban agglomeration in northern China - Zhongxiu Zhen; Linhao Guo; Fei Xie; Liang Li; Xingjun Zhou; Chunyu Wu; Frank Yonghong Li; Jinyuan Xin; Changwei Lü (Atmospheric Research, 2026)

Preparation and mechanism of Fe3+ modified layered double hydroxides with surfactants for inhibiting the entire process of coal spontaneous combustion - Linhao Xie; Hongqing Zhu; Tianyu Li; Binrui Li; Houwang Wang; Jiahao Duan; Lei Zhang (Process Safety and Environmental Protection, 2025)

3D reconstruction of pore throat connectivity in Shale: An SAXS-MICP integrated framework - Linhao Zhang; Shu Jiang; Jiale Fu; Fei Xie; Zhile Han; Zihao Li; Mengdi Sun (Marine and Petroleum Geology, 2025)

Research on Conflict Detection Methods in Detailed Design of Large Cruise Ships - Feihui Yuan; Jinghua Li; Yiying Wang; Linhao Wang; Qi Zhou; Dening Song (Journal of Marine Science and Engineering, 2025)
Aiming to address the frequent design conflicts arising during multi-disciplinary collaboration in the detailed design phase of large cruise ships, coupled with the inadequacy of traditional methods in detecting unknown constraints, this paper proposes a hybrid conflict detection framework integrating interval propagation with intelligent algorithms. First, using the piping design of a cruise ship’s water supply system as a typical scenario, design constraints are categorized into known and unknown sets. For known constraints, the interval propagation algorithm is employed for rapid inference and verification. For unknown constraints that are difficult to express explicitly, an improved particle swarm optimization (IPSO) algorithm is proposed to optimize the parameters of a radial basis function (RBF) neural network, thereby constructing an IPSO-RBF conflict detection model. Case studies demonstrate the interval propagation algorithm’s efficacy in identifying conflicts within water supply pipeline designs. Concurrently, testing against historical design datasets reveals that the IPSO-RBF model outperforms multiple comparative models, including PSO-RBF, AFSA-RBF, etc., in terms of conflict detection accuracy, precision, and recall. This validates the method’s effectiveness and superiority in resolving design conflicts within complex systems for large cruise ships.

Tannic acid-mediated covalent adaptable networks in chitosan-collagen coatings: Toward on-demand peelable superhydrophobic textiles with enhanced durability - Hui Li; Xin Lin; Yinghui Wang; Maxiaoqi Zhu; Linhao Cai; Yingjie Cai; Vincenzo Naddeo (Chemical Engineering Journal, 2025)

Construction of island ecological security pattern under multi-circle development pattern: Evidence from Hainan Island - Sizheng Li; Feng Gui; Hongyu Li; Yanwei Song; Linhao Peng; Lin Zhou; Yang Wang (Ocean & Coastal Management, 2025)

Effects of NGF-chitosan on alleviating secondary degeneration and repairing primary degeneration after expanded partial optic nerve transection - Xiao Liu; Hongmei Duan; Limin Gao; Linhao Yuan; Peng Hao; Wen Zhao; Yudan Gao; Zitian Huang; Xi Wang; Wenjianlong Zhou; Shunchang Ma; Ningli Wang; et al. (Science China Life Sciences, 2025)

Microscopic understanding of the reaction path and gas production mechanism of key functional groups in coal: Combination of molecular dynamics, quantum chemistry and experimental research - Binrui Li; Hongqing Zhu; Lei Zhang; Rui Li; Linhao Xie; Erhui Zhang; Baolin Qu; Lintao Hu (Fuel, 2025)

Experimental and quantum chemical study of synergistic inhibitor based on physicochemical interaction in the prevention of coal spontaneous combustion - Hongqing Zhu; Jiashuo Wang; Rui Li; Linhao Xie; Lei Zhang; Erhui Zhang; Lintao Hu (Fuel, 2025)

Study on compressive strength characteristics of lime-fly ash composite improved mottled red clay - Xiushao Zhao; Qi Deng; Qijing Yang; Linhao Zhao; Zhijie Zhou; Yunfan Li (Arabian Journal of Geosciences, 2025)

Modes of occurrence of rare earth elements and yttrium in the subbituminous coal of the Jungar Coalfield, Ordos Basin, North China - Bo Jiu; Zhijun Jin; Huidi Hao; Zhaoguo Wang; Wenhui Huang; Zhenguang Shang; Runchao Liu; Yang Li; Linhao Huang; Binchao Qin; Zixuan Huang; Li Long; et al. (International Journal of Coal Geology, 2025)

Microstructural Changes and Kinetic Analysis of Oxidation Reaction in Coal–Oil Symbiosis - Lintao Hu; Hongqing Zhu; Binrui Li; Rui Li; Linhao Xie; Ruoyi Tao; Baolin Qu (Natural Resources Research, 2025)

Combined skin injury model from airblast overpressure and seawater immersion in rats: establishment, characterization, and mechanistic insights - Jinpeng Du; Zhao Li; Yi Kong; Wei Song; Zhongming Chen; Mengde Zhang; Yuyan Huang; Chao Zhang; Xu Guo; Linhao Hou; Yaxin Tan; Liting Liang; et al. (Journal of Molecular Histology, 2025)

Preparation of Mg/Al-LDH@HC composite with low concentration hydrochloric acid modified for phosphate removal from aqueous solution: Synthesis, adsorption performance and mechanism - Xiaojuan Zhang; Ting Dong; Linhao Wang; Tianhua Yang; Yanlong Li; Wanli Zhang (Journal of Environmental Management, 2025)

Building the bimetallic site of Co2Mo3O8/Co9S8 heterojunction via interface electronic reconfiguration to enhance peroxymonosulfate activation for singlet oxygen formation - Jiamei Li; Jia Wei; Jihong Sun; Jiangkai Huo; Yanan Li; Nan Cui; Linhao Wang; Wei Ji; Qi Jing; Jun Li; Ju Wang (Chemical Engineering Journal, 2025)

Efficient glycyrrhetinic acid biomanufacturing through protein engineering and dual-GUS combination strategy with novel β-glucuronidase from Aspergillus calidoustus CLH-22 - Linhao Chen; Junjie Lai; Yan Luo; Tao Shu; Bo Lv; Chun Li (Bioresource Technology, 2024)

Quantitative analysis of the sensitivity and spatial stratified heterogeneity of extreme precipitation across river basins - Ruixin Duan; Linhao Zhong; Guohe Huang; Yongping Li; Feng Wang (Journal of Hydrology, 2024)

Oxidative reactivity of MgCl2 solution treated coal at different oxidation stages based on physical and chemical microstructure - Linhao Xie; Hongqing Zhu; Houwang Wang; Binrui Li; Baolin Qu; Tianyu Li; Rui Li (Fuel, 2024)

Navigating highly reversible Zn metal anodes via a multifunctional corrosion inhibitor-inspired electrolyte additive - Buxin Ma; Kun Zhang; Linhao Li; Renjie Jia; Bingbing Wang; Quan Ji; Xiaojing Long; Jinkui Feng; Liwen Tan (Chemical Engineering Journal, 2024)

Three birds with one stone: A nano zeolitic imidazolate framework-luciferase-antimicrobial peptide biocomposite-based biosensing platform for improving enzyme stability, detection sensitivity, and sterilization effect - Renjie Zhou; Tingting He; Linhao Peng; Dengfeng Li; Zhenzhong Yu; Xin Yang; Ning Gan (Chemical Engineering Journal, 2024)

Analysis of the water temperature and quality characteristics of the Daheiting Reservoir based on coupled hydrology–hydrodynamic–water quality simulations - Ting Zhang; Linhao Wang; Binxin Xu; Jianzhu Li; Ping Feng (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Seasonal variations of Arctic cloud in recent 14 years using CALIPSO-GOCCP - Zhina Jiang; Minghu Ding; Linhao Zhong; Yijiao Li; Xia Hu (Atmospheric Research, 2024)

Cyanobacterial and fungi-like microbial fossils from the earliest Cambrian phosphorite of South China - Linhao Cui; Wei Liu; Jinhua Li; Xingliang Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Enhanced organic contaminant eradication using boron-doped bimetallic cathodes in electro-Fenton: Unveiling structure–activity relationship - Wei Ji; Jia Wei; Mengdie Xu; Linhao Wang; Jiangkai Huo; Yanan Li; Nan Cui; Jiamei Li; Xueru Cui; Zijian Jiang; Xiruo Niu; Jun Li (Chemical Engineering Journal, 2024)

Nanoscale characterization of Ediacaran microfossils from lower Doushantuo formation chert nodules - Shiqi Cheng; Lianjun Feng; Chaoqun Zhang; Linhao Cui; Wei Liu; Hao Qiu; Shi He; Xuelei Chu; Xingliang Zhang; Jinhua Li (Chemical Geology, 2024)

New insights into the pH-dependent removal of sulfamethoxazole in peracetic acid activation systems: From mechanistic exploration to practical application potentials - Xiruo Niu; Jia Wei; Zijian Jiang; Xueru Cui; Yanan Li; Nan Cui; Jiamei Li; Linhao Wang; Jiangkai Huo; Wei Ji; Xiaohui Zhang; Jun Li (Journal of Hazardous Materials, 2024)

The Cambrian microfossil Qingjiangonema reveals the co-evolution of sulfate-reducing bacteria and the oxygenation of Earth’s surface - Linhao Cui; Kelei Zhu; Ruiyun Li; Chao Chang; Laiyuan Wu; Wei Liu; Dongjing Fu; Peiyu Liu; Hao Qiu; Guoqiang Tang; Qiuli Li; Robert R. Gaines; et al. (Science Bulletin, 2024)

Plant–virus arms race beyond RNA interference - Linhao Ge; Xueping Zhou; Fangfang Li (Trends in Plant Science, 2024)

Highly dispersed Fe7S8 anchored on sp2/sp3 hybridized carbon boosting peroxymonosulfate activation for enhanced EOCs elimination though singlet oxygen-dominated nonradical pathway - Zijian Jiang; Jia Wei; Xiruo Niu; Xueru Cui; Yanan Li; Nan Cui; Jiamei Li; Jiangkai Huo; Linhao Wang; Wei Ji; Jun Li (Journal of Hazardous Materials, 2024)

m6A modification of plant virus enables host recognition by NMD factors in plants - Hao He; Linhao Ge; Yalin Chen; Siwen Zhao; Zhaolei Li; Xueping Zhou; Fangfang Li (Science China Life Sciences, 2024)

A state-of-the-art review on heterogeneous catalysts-mediated activation of peracetic acid for micropollutants degradation: Classification of reaction pathways, mechanisms, influencing factors and DFT calculation - Linhao Wang; Jia Wei; Yanan Li; Jiangkai Huo; Wei Ji; Nan Cui; Jiamei Li; Xiruo Niu; Zijian Jiang; Xueru Cui; Jun Li (Chemical Engineering Journal, 2023)

Plant and animal positive-sense single-stranded RNA viruses encode small proteins important for viral infection in their negative-sense strand - Pan Gong; Qingtang Shen; Mingzhen Zhang; Rui Qiao; Jing Jiang; Lili Su; Siwen Zhao; Shuai Fu; Yu Ma; Linhao Ge; Yaqin Wang; Rosa Lozano-Durán; et al. (Molecular Plant, 2023)

Prediction of the soil water content in the Luanhe river basin based on CMIP6 - Ting Zhang; Linhao Wang; Jianzhu Li; Ping Feng (Journal of Cleaner Production, 2023)

Torsional Optical Fiber Stress Analysis and Vortex-Induced Vibration Study of Three-Core Submarine Cable - Haotian Tan; Yanpeng Hao; Peng Zhang; Qishun Li; Wanxing Tian; Linhao Chen; Lin Yang; Licheng Li (Journal of Marine Science and Engineering, 2023)
Due to current scouring, submarine cables are prone to be exposed, suspended, and even vortex-induced vibration, which is not conducive to the safe operation of the power grid. In this contribution, the finite element simulation model of a 35 kV three-core optical fiber composite submarine cable with a suspended span length of 9.5 m is established. The natural frequency of the model is obtained through modal analysis. Then the vortex-induced vibration is simulated by the fluid–structure coupling method, and the stress distribution and change law of the torsional optical fiber is extracted. The results show that in the submarine cable, there appears to be a beating vibration and locking phenomena respectively, under two flow velocities. The transverse vibration amplitude of the latter increases significantly due to a resonance state. When the flow direction is perpendicular to the submarine cable, the stress distribution of the torsional optical fiber at the initial moment and at the 1/2 T moment of a vibration cycle approximately represents a mirror image relationship. In addition, the frequency of the stress change is the same as the frequency of the vortex-induced vibration, which can judge whether the vortex-induced vibration occurs. Moreover, the vortex-induced vibration range can be determined by the maximum stress change location.

Intensified lacustrine turbidite deposition as a response to the Carnian Pluvial Episode: Insights from the Triassic Ordos Basin in North China Plate - Peng Chen; Benzhong Xian; Meijun Li; Linhao Fang; Naveed Ur Rahman; Jianping Liu; Sirui Chen; Rongheng Tian; Qianran Wu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Cyclostratigraphy of the Lower Jurassic (Toarcian) terrestrial successions in the Sichuan Basin, southwestern China - Ruoyuan Qiu; Linhao Fang; Yuanzheng Lu; Yuxuan Chen; Renda Huang; Wenzhi Lei; Pengyuan Zhang; Mingsong Li (Journal of Asian Earth Sciences, 2023)

Effects of portable air filtration on submicrometer- and micrometer-sized particle deposition and concentration in a natural ventilated skilled nursing facility - Linhao Li; Zachary C. Pope; Youngjoo Son; Stephanie M. Eilts; Christopher J. Hogan; Meng Kong (Building and Environment, 2023)

Numerical Study of the Local Scouring Process and Influencing Factors of Semi-Exposed Submarine Cables - Qishun Li; Yanpeng Hao; Peng Zhang; Haotian Tan; Wanxing Tian; Linhao Chen; Lin Yang (Journal of Marine Science and Engineering, 2023)
Local scouring might result in the spanning of submarine cables, endangering their mechanical and electrical properties. In this contribution, a three-dimensional computational fluid dynamics simulation model is developed using FLOW-3D, and the scouring process of semi-exposed submarine cables is investigated. The effects of the sediment critical Shields number, sediment density, and ocean current velocity on local scouring are discussed, and variation rules for the submarine cables’ spanning time are provided. The results indicate that three scouring holes are formed around the submarine cables. The location of the bottom of the holes corresponds to that of the maximum shear velocity. The continuous development of scouring holes at the wake position leads to the spanning of the submarine cables. The increase in the sediment’s critical Shields number and sediment density, as well as the decrease in the ocean current velocity, will extend the time for maintaining the stability of the upstream scouring hole and retard the development velocity of the wake position and downstream scouring holes. The spanning time has a cubic relationship with the sediment’s critical Shields number, a linear relationship with the sediment density, and an exponential relationship with the ocean current velocity. In this paper, the local scouring process of semi-exposed submarine cables is studied, which provides a theoretical basis for the operation and maintenance of submarine cables.

SUMOylation-modified Pelota-Hbs1 RNA surveillance complex restricts the infection of potyvirids in plants - Linhao Ge; Buwei Cao; Rui Qiao; Hongguang Cui; Shaofang Li; Hongying Shan; Pan Gong; Mingzhen Zhang; Hao Li; Aiming Wang; Xueping Zhou; Fangfang Li (Molecular Plant, 2023)

Graphdiyne oxide elicits a minor foreign-body response and generates quantum dots due to fast degradation - Lizhen Wang; Yang Zhang; Linhao Li; Xuezheng Geng; Dandan Dou; Lu Yu; Haoyu Jing; Yubo Fan (Journal of Hazardous Materials, 2023)

Insight into boron-doped biochar as efficient metal-free catalyst for peroxymonosulfate activation: Important role of -O-B-O- moieties - Guoping Pan; Jia Wei; Mengdie Xu; Jiamei Li; Linhao Wang; Yanan Li; Nan Cui; Jun Li; Zhaoxu Wang (Journal of Hazardous Materials, 2023)

High-consistency proton exchange membrane fuel cells enabled by oxygen-electron mixed-pathway electrodes via digitalization design - Zhiming Bao; Biao Xie; Weizhuo Li; Shenghui Zhong; Linhao Fan; Chasen Tongsh; Fei Gao; Qing Du; Mohamed Benbouzid; Kui Jiao (Science Bulletin, 2023)

Bibliometrics and visualization analysis of research in the field of sustainable development of the blue economy (2006–2021) - Jinshui Liang; Zengqiang Yin; Jun Yang; Yuan Li; Min Xu; Jiaxing Li; Min Yang; Linhao Niu (Frontiers in Marine Science, 2022)
The blue economy is the sustainable use of ocean resources for economic growth, improved livelihoods, and jobs while preserving the health of the ocean ecosystem. In order to completely address the three dimensions of development, social, economic, and environmental in an integrated manner from 2015 to 2030, and to shift to a sustainable development path, the United Nations has formulated 17 global Sustainable Development Goals (SDGs), of which SDG14 is directly associated with the blue economy, which is also an essential material foundation for achieving other SDGs. In particular, the blue economy with the theme of sustainable and high-quality development of the marine economy will provide the possibility and important material guarantees for the eradication of poverty (SDG1), the eradication of hunger (SDG2), and the reduction of inequalities within and among countries (SDG10). In this study, CiteSpace and VOSviewer were used to visualize and analyze the global blue economy sustainability research field from 2006 to 2021, obtaining institutions, countries, cited authors, cited literature, journals, keywords, and clustered knowledge graphs. The results show that most of the blue economy sustainable development research is independent, with less cooperation among institutions. The research focuses on four research themes: fundamental theory and development direction, ecological and environmental sustainability, marine development methods, and comprehensive benefits and functions; the dynamics of the blue economy sustainable development research field is summarized.

Frequent central Pacific La Niña events may accelerate Arctic warming since the 1980s - Jing Li; Lin Mu; Linhao Zhong (Acta Oceanologica Sinica, 2021)

Microcracks on the Rat Root Surface Induced by Orthodontic Force, Crack Extension Simulation, and Proteomics Study - Shengzhao Xiao; Linhao Li; Jie Yao; Lizhen Wang; Kaimin Li; Chongshi Yang; Chao Wang; Yubo Fan (Annals of Biomedical Engineering, 2021)

Molecular characterization of structural protein genes of dengue virus serotype 1 epidemic in Yunnan, Southwest China, in 2018 - Qingping Lan; Yun Shu; Linhao Li; Xiyun Shan; Dehong Ma; Tingting Li; Xiaodan Wang; Yue Pan; Junying Chen; Juan Zhang; Pinghua Liu; Qiangming Sun (Archives of Virology, 2021)

Distinct tropical Pacific sea surface temperature anomaly regimes enhanced under recent global warming - Jing Li; Lin Mu; Linhao Zhong (International Journal of Climatology, 2021)
El Niño and Southern Oscillation (ENSO) events are usually monitored by tropical Pacific sea surface temperature anomaly (SSTA) patterns with dramatic impacts on the global climate. To explore the diversity of the tropical Pacific SSTA, a novel method combined empirical orthogonal function analysis and the K‐means clustering algorithm is carried out to classify SSTA patterns during 1950–2016. Meanwhile, the total distance variance and total silhouette value are introduced to determine an optimal number of distinguishable representative SSTA patterns. Ten SSTA patterns are obtained, which shows frequent basin‐wide warming and extreme cold ENSO events in recent decades. It may be attributed to the changes in composition of the intrinsic modes along with the background mode of slowly increasing east–west SST gradient. The comparative analysis between periods 1950–1969 and 1997–2016 suggests that the two regimes of tropical Pacific SSTA, featured as extreme warm and moderate warm/extreme cold patterns respectively, become more distinct under recent global warming.

Anchoring of atmospheric teleconnection patterns by Arctic Sea ice loss and its link to winter cold anomalies in East Asia - Muyuan Li; Dehai Luo; Ian Simmonds; Aiguo Dai; Linhao Zhong; Yao Yao (International Journal of Climatology, 2021)
In this paper, the physical processes underlying recent winter cold anomalies over East Asia (EA) are examined via statistical analysis. It is found that the EA cold anomaly depends on the warming in the North Atlantic, sea ice loss in the Barents–Kara Sea (BKS), and atmospheric teleconnection patterns. Specifically, the sea ice loss in the BKS can anchor teleconnection patterns originating from different North Atlantic sea surface temperature (SST) patterns. Different patterns of North Atlantic warming can affect the position of the cold anomaly region through altering the atmospheric circulations. In addition, whether the relevant teleconnection pattern leads to enhanced cold anomaly over EA crucially depends on the sea ice loss in the BKS, because it can anchor the blocking anticyclone embedded in the teleconnection pattern over the Ural region and make it more persistent and quasi‐stationary. Furthermore, it is found that the role of SST modes in the EA cold anomaly depends on their time scales. Although the strong basin‐scale warming (north–south SST tripolar mode) in the North Atlantic mid‐ to high‐latitudes plays a major role in decadal (interannual) cold anomaly over EA, it appears that the Atlantic east–west SST dipole structure dominates winter temperature variations over EA in recent decades on both the interannual and decadal time scales.

Mechano growth factor pretreatment yield mechanical stimuli induced cell stress responses in ligament fibroblasts of osteoarthritis via activating ATF-2 - Yu Ma; Yang Song; Linhao Li; Lili Dong; Chunli Wang; Pingping Wang; Li Yang (Biotechnology Letters, 2020)

Large‐scale atmospheric circulation control of summer extreme hot events over China - Muyuan Li; Dehai Luo; Yao Yao; Linhao Zhong (International Journal of Climatology, 2020)
A large‐scale high air temperature event in China during July 2017 is examined using observational reanalysis data. Based on this case study, summer extreme hot events (EHEs) over China are classified into five types using the self‐organizing map (SOM) method. The five EHE types include those over northeast China (NEC type), northwest China (NWC type), north China (NC type), mid‐eastern China (MEC type) and south China (SC type). All types are associated with sustainable anticyclones (EHE anticyclones). Composite analysis shows that the EHE anticyclone in northern China (corresponding to the NEC, NWC and NC types) is primarily formed by downstream wave train propagation from upstream blocking, while EHE anticyclone formation in southern China (corresponding to the MEC and SC types) is driven by the joint action of downstream wave train propagation and westward movement of the western Pacific subtropical high. Moreover, the upstream blocking and downstream EHE anticyclone embedded in the wave train play important roles in maintaining the wave train. The upstream blocking acts as an energy source for downstream EHE anticyclone intensification and leads to EHE formation, with the intensified zonal wind at certain latitudes affecting the wave train propagation direction. This finding indicates that the upstream blocking with intensified zonal wind at certain latitudes may serve as an indicator for the prediction of EHE anticyclones over China. As a consequence of the persistent EHE anticyclone, the land surface is primarily warmed by enhanced shortwave radiation through reduced regional cloud cover. For the NWC and NC types, heating of the lower atmosphere takes place via the sensible heat flux; whereas, for the NEC, MEC and SC types, the main heating terms are the latent heat flux, sensible heat flux and upward longwave radiation.

Metformin Disrupts Bile Acid Efflux by Repressing Bile Salt Export Pump Expression - Brandy Garzel; Tao Hu; Linhao Li; Yuanfu Lu; Scott Heyward; James Polli; Lei Zhang; Shiew-Mei Huang; Jean-Pierre Raufman; Hongbing Wang (Pharmaceutical Research, 2020)

Identification of Novel Activators of Constitutive Androstane Receptor from FDA-Approved Drugs by Integrated Computational and Biological Approaches - Caitlin Lynch; Yongmei Pan; Linhao Li; Stephen S. Ferguson; Menghang Xia; Peter W. Swaan; Hongbing Wang (Pharmaceutical Research, 2013)

The Role of Constitutive Androstane Receptor in Oxazaphosphorine-Mediated Induction of Drug-Metabolizing Enzymes in Human Hepatocytes - Duan Wang; Linhao Li; Jennifer Fuhrman; Stephen Ferguson; Hongbing Wang (Pharmaceutical Research, 2011)

Bioactive Terpenoids and Flavonoids from Ginkgo Biloba Extract Induce the Expression of Hepatic Drug-Metabolizing Enzymes Through Pregnane X Receptor, Constitutive Androstane Receptor, and Aryl hydrocarbon Receptor-Mediated Pathways - Linhao Li; Joseph D. Stanton; Antonia H. Tolson; Yuan Luo; Hongbing Wang (Pharmaceutical Research, 2009)